Endogenous pain modulation in children with functional abdominal pain disorders. Issue 8 (August 2019) - Pas, Roselien; Rheel, Emma; Van Oosterwijck, Sophie; Leysen, Laurence; Van De Vijver, Els; Nijs, Jo; Ickmans, Kelly; Meeus, Mira
Abstract : Abstract: Functional abdominal pain disorders (FAPDs) are common among young individuals. To date, relatively little is known regarding the function of the endogenous analgesic mechanisms in this vulnerable group. Therefore, this case–control study aimed to compare conditioned pain modulation (CPM), pressure algometry, and psychosocial variables in 39 young children (aged 6-12 years) with FAPD and 36 age- and sex-matched pain-free controls. Pressure algometry was used to assess pressure pain thresholds (PPTs) at both symptomatic (umbilicus) as remote (trapezius and tibia) test sites. Conditioned pain modulation was recorded as an increase in the PPT at the trapezius test site in response to experimental conditioning pain imposed by the cold pressor task (12 ± 1°C). The assessors were blinded to the diagnoses. Parent-proxy and/or self-reported questionnaires were used to assess child's pain intensity, functional disability, pain-related fear, and parental pain catastrophizing. Compared with pain-free controls, young children with FAPD showed lower PPTs at all test sites ( P < 0.05), a lower CPM response ( P = 0.02), more functional disability ( P < 0.001), and pain-related fear ( P < 0.001). Parents of children with FAPD catastrophized more about their child's pain than parents of healthy children ( P < 0.001). No sex differences were found for the experimental pain measurements ( P > 0.05), nor was there a significant correlation between the child- and parent-reported questionnaires and the CPM effect ( P > 0.05). In summary, young children with FAPD demonstrated secondary hyperalgesia and decreased functioning of endogenous analgesia. Abstract : Young children with functional abdominal pain disorders have less-efficient endogenous analgesia and demonstrate secondary hyperalgesia compared with healthy age- and sex-matched controls.